Pengaruh Pengungkapan ESG dan Kepemilikan Institusional terhadap Kinerja Keuangan: Intensitas Kompetisi Pasar sebagai Variabel Moderasi pada Perusahaan Terindeks SRI-KEHATI Periode 2019-2024 - Mochammad Ramlan; Tri Neliana (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
SRI-KEHATI Index is known as an index that includes companies with a strong commitment to sustainability principles. However, in practice, not all companies included in the index are able to maintain stable or positive financial performance. such as PT Pembangunan Jaya Ancol Tbk (PJAA), which recorded losses of IDR 393 billion in 2020 and IDR 276 billion in 2021, as well as PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO), which experienced a decline in profitability of IDR 156 billion in 2022 and IDR 154 billion in 2023. This study was conducted to analyze the effect of ESG and institutional ownership on financial performance with market competition intensity as a moderating variable in companies included in the SRI-KEHATI index during the 2019-2024 period. The population in this study included all companies indexed in SRI-KEHATI during the 2019-2024 period, with a sample size of eight companies selected using purposive sampling. This study utilized secondary data from company annual reports and sustainability reports for the 2019-2024 period. The analysis technique used in this study was multiple linear regression. The results of the study show that: first, ESG has no effect on financial performance; second, institutional ownership affects financial performance; third, market competition intensity does not moderate the effect of ESG and institutional ownership on financial performance.